Ascension Theology and Habakkuk A Reformed Ecclesiology in Filipino American Perspective - Presa, Neal D. (Asian Christianity in the Diaspora, 2018)
This book describes Reformed ecclesiology through the lived faith of the Filipino American Christian diaspora. It proposes a contextual, constructive ecclesiology by engaging with the Presbyterian/Reformed theological tradition's understanding of the ascension of Jesus Christ with the Old Testament book of Habakkuk as a conversation partner. .